The Effect Of Students Motivation Toward Students Achievement Grade V At Elementary School Kecamatan Rambah Hilir Kabupaten Rokan Hulu Riau - Pendidikan Guru Madrasah Ibtidaiyah (Prodi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan UIN Sulthan Thaha Saifuddin Jambi, 2019)
ABSTRACT This study aims to reveal the effect of learning motivation on learning outcomes in grade V elementary school District of Rambah Hilir District, Rokan Hulu Riau Regency. The hypothesis in this study, learning motivation has an effect on learning outcomes. This type of research is correlation and regression. The research method used is correlational quantitative methods. The study population was all fifth grade students of State Elementary Schools in Cluster IV in Rambah Hilir Subdistrict, Rokan Hulu Regency, totaling 207 people. 67 results were determined using thetechnique Stratified Proportional Random Sampling. The data was collected with a Likert scale model questionnaire that had been tested for validity and reliability. The results of the questionnaire trial obtained by the variable X 0.859> 0.396 by comparing r count greater than r table, the variable is said to be reliable / valid. Data were analyzed by correlation and regression techniques. The results of the analysis showed that the magnitude of the influence of motivation on learning outcomes was 11.7%.